Stressors and coping strategies in hemodialysis patients - (:unkn) unknown (My University, 2009)
Objectives: The aim of the study was to determine relationships among treatment-related stressors and coping strategies of chronic hemodialysis patients. Methodology: The sample of this study consisted of 224 participants. Data was collected with Hemodialysis Stressors Scale and Carver Coping Scale and analysed by using the linear multiple regression analysis. Results: The most frequent stressors reported were: limitation of vacation (80.4%), followed by fatigue (79.9%) and uncertainty about future (79.0%). The most frequently used coping strategies were turning to religion, active coping and suppression of competing activities. Physical treatment-related stressors were significantly related to behavioural disengagement. Conclusions: This study shows that the most frequently used coping strategy is "turning to religion" by hemodialysis patients which is different from previous studies. The Turkish view the belief as the basic and most important aspect of human life so the belief of affects of coping in our country are different from the Western World.
Keywords: Coping strategies; Hemodialysis; Stressors